Biodegradation of expanded and extruded polystyrenes by using Zophobas morio larvae - Tay, Jun Hoe (2022)
Malaysia faces a significant challenge in managing plastic trash, particularly non-recycled or illegally disposed of plastic wastes. Polystyrene (PS) is marked with a plastic resin number code of 6, which denotes that it is recyclable, but less recycled due to the costs and complicated recycling procedure. PS garbage pollutes the environment and poses a significant health risk to humans, animals and the marine ecology. PS consists of expanded (EPS) and extruded (XPS). EPS has a low density and low water diffusion resistance while XPS has a high density and high-water diffusion resistance. A recent study found that Zophobas morio larvae can be acts as a potential biodegradation agent in degrading PS wastes. Thus, first objective is to determine the growth development of Z. morio under controlled lab conditions. It was discovered that Z. morio go through a complete metamorphosis with four stages of growth: egg, larvae, pupa, and adult. Most importantly, it was noticed that larval stages can growth up to 190 ± 6 days. Larval stages are undergoing early instar, mid instar and late instar consists of 18 larval instars end up with 35.91 ± 4.12 mm larvae length, 3.88 ± 0.41 mm head capsule width and weight of 369.0 ± 81.9 mg. The growth development of other stages was also recorded to utilize it as a guideline for commercial production. A study showed that supplement added in larvae diets could enhance EPS and XPS degradation. Thus, second objective is to evaluate the effectiveness of degradation on EPS and XPS with different supplements diets using Z. morio larvae. The highest EPS and XPS consumption were found in oatmeal diets with 422.30 ± 2.44 mg and 268.33 ± 11.08 mg respectively. A molecular weight (Mw and Mn) was identified through GPC indicated that EPS and XPS molecular weight were reduced. 1H NMR and FTIR analyses further proven depolymerization and partial oxidation of EPS and XPS occurred in all feeding diets. In overall, the efficiency of supplement on EPS and XPS degradation with ascending order such as cornmeal, wheat bran, oatmeal accordingly. Whilst, the following objectives is to investigate the growth development of Z. morio larvae after consuming expanded and extruded polystyrene with different diets. Results showed that larvae length (42.44 ± 2.50 mm), number of instars (17 ± 1 instars) and duration of larval (157 ± 6 days) was found in oatmeal as a supplement diet contains EPS foam which is opposed to control diets. Same phenomena were occurred in XPS foam diets. This indicate that sufficient nutrient provided may enhance larvae growth, reduce larval instar number and shorten larval development period. Lastly, oatmeal as a supplement diet with EPS and XPS were used to study microbial population in the gut system of Z. morio larvae. Analysis of gut microbiome by next-generation sequencing revealed that Kluyvera spp., Klebsiella spp., and Enterobacter spp. was showed closely associated in EPS and XPS degradation. Supplements added enhance larvae growth and assisting larvae degrade EPS and XPS wastes.